Solubility of Famotidine in Supercritical Carbon Dioxide: Experimental Measurement and Thermodynamic Modeling - Rojas-Sepulveda, A (Elsevier B.V., 2023)
In the current study, the solubility of famotidine (FAM) in supercritical carbon dioxide (scCO₂) was experimentally determined for the first time. The FAM solubility in scCO₂, expressed as mole fraction, at different temperatures (308 − 338 K) and pressures (12 − 30 MPa) was found to be in the range of 1.40 × 10−6 to 1.11 × 10−4. Due to the low solubility of FAM in scCO₂, the gas anti-solvent and supercritical anti-solvent processes can be a good option to generate the nano/micro size particles of this drug. The experimental solubility data were correlated by the density-based models of Bartle et al., Méndez-Santiago and Teja (MST), Jouyban et al. and Hozhabr et al., by the non-cubic equation of state PC-SAFT, and by the two versions of the Estévez et al. model (ECM-PR and ECM-RK). According to the modeling results, the Estévez et al. model showed the highest accuracy with AARD values of 9.92 (ECM-PR) and 10.70 (ECM-RK). The empirical models also yielded satisfactory outcomes to the correlation of the solubility of FAM in scCO₂. © 2023 Elsevier B.V.